2011
DOI: 10.1111/j.1365-2427.2010.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river ice on riparian vegetation

Abstract: 1. Many rivers and streams experience pronounced ice dynamics caused by the formation of anchor and frazil ice, leading to flooding and disturbance of riparian and aquatic communities. However, the effects of dynamic ice conditions on riverine biota are little known. 2. We studied the formation of anchor ice in natural streams over 2 years and assessed the effects of anchor ice on riparian vegetation by comparing sites with frequent or abundant and little or no anchor ice formation. We also studied the direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…A number of frosttolerant plant species can survive under an ice cover or endure total enclosure in ice for several months, thereby giving these species an advantage over annuals, as they already occupy the habitats when the ice melts (Renman, 1989a). Engström et al (2011) showed that plants with budding parts overwintering above the ice sheet had less chance of survival than plants with overwintering organs close to or in the ground. They tested the survival of Vaccinium vitis-idaea (a dwarf shrub with overwintering budding parts aboveground), Filipendula ulmaria (a forb with budding parts underground) and Dechampsia cespitosa (a tussock-forming grass with budding parts at the soil surface).…”
Section: (B) Physiological Stressmentioning
confidence: 98%
See 4 more Smart Citations
“…A number of frosttolerant plant species can survive under an ice cover or endure total enclosure in ice for several months, thereby giving these species an advantage over annuals, as they already occupy the habitats when the ice melts (Renman, 1989a). Engström et al (2011) showed that plants with budding parts overwintering above the ice sheet had less chance of survival than plants with overwintering organs close to or in the ground. They tested the survival of Vaccinium vitis-idaea (a dwarf shrub with overwintering budding parts aboveground), Filipendula ulmaria (a forb with budding parts underground) and Dechampsia cespitosa (a tussock-forming grass with budding parts at the soil surface).…”
Section: (B) Physiological Stressmentioning
confidence: 98%
“…The composition and distribution of riparian (Auble & Scott, 1998;Ettema, 2002) and aquatic vegetation (Dayton, Robilliard & Devries, 1969;Erixon, 1981) have been linked to ice disturbance and stress (Uunila, 1997;Engström et al, 2011). The literature describes two major ways in which ice formation and break-up affect vegetation: physical disturbance and physiological stress.…”
Section: Ice Effects On Vegetationmentioning
confidence: 98%
See 3 more Smart Citations